Diagnostic performances of serum liver enzymes and cytokines in non-alcoholic fatty liver disease. Issue 1 (2015) - Turkon, Hakan; Colak, Ayfer; Toprak, Burak; Yıldız, Coskun; Hasturk, Aybike; Yıldız, Ömür; Binnetoglu, Emine; Yener, Özlem
No abstract available